Penggunaan Analisis Multidimensional Scaling Untuk Mengetahui Kemiripan Rumah Sakit Swasta Yang Ada di Jakarta Selatan Berdasarkan Karakteristik Pelanggan - Nasihardani, Dana; Satrio, Renno; Khairullah, M. Fikri; Abdurahman, Ridwan; Pambengkas, Rahid (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
The hospital is an institution that supports the implementation of health services. Hospitals in Indonesia are very much started from the private and public levels. The number of these hospitals makes it difficult for the community to differentiate between them. The purpose of this study was to obtain customer descriptions of private hospitals and to find out the similarities between the private hospitals that were used as research objects. The method used is Multidimensional Scaling (MDS). MDS is a multiple variable technique that can be used to determine the position of another object based on its similarity assessment. The results of the Multidimensional Scaling analysis map can be seen that the private hospitals Metropolitan Medical Center Hospital and Jakarta Hospital have a level of similarity in the availability of complete medicines because of their close proximity to each other. As for Tebet Hospital, Medistra Hospital, and Mayapada Kuningan Hospital, South Jakarta, they are relatively far from one another, which means that these three hospitals have no resemblance or dissimilarity.